Automated and advanced document processing system in the woodworking industry - Panfilov I.A.; Lobkow K.Y.; Kleshko I.I.; Masiuk M.A.; Nikolaev S.V. (BIO Web of Conferences, 2024)
This article presents a detailed framework for the seamless integration of a new document processing system within the operational workflow of a company. The proposed plan prioritizes both continuity and parallel deployment to ensure minimal disruption during implementation. It includes a thorough decomposition of system use cases, illustrated with block diagrams, along with sample mock-ups of the user interface to facilitate understanding among developers, designers, and technical writers throughout the development process. The primary objectives of this initiative are to boost employee productivity, reduce costs associated with production downtime, and guarantee the system’s scalability to meet evolving document processing demands.